2021
DOI: 10.1039/d0nj04128a
|View full text |Cite
|
Sign up to set email alerts
|

Phenol removal from wastewater by CWPO process over the Cu-MOF nanocatalyst: process modeling by response surface methodology (RSM) and kinetic and isothermal studies

Abstract: Water-stable metal–organic frameworks (MOFs), which possess unique porous structures, have attracted attention from scientists exploring novel and efficient methods for the elimination of phenol compounds from aqueous media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…For instance, Gholipoor et al studied Cu/UiO-66 as heterogeneous catalysts for the efficient CWPO of phenol wastewater. 22 Zhao et al investigated surface oxygen vacancy (OVs)-modified Bi 2 MoO 6 /MIL-88B(Fe) heterostructures as a catalyst for dye pollutant rhodamine B (RhB) and model colorless pollutant bisphenol A (BPA) photodegradation. 23 In our previous studies, UiO-66 was used as a catalyst in CWPO and showed excellent catalytic effect ( X phenol = 95%, X H 2 O 2 = 55% in 60 min).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Gholipoor et al studied Cu/UiO-66 as heterogeneous catalysts for the efficient CWPO of phenol wastewater. 22 Zhao et al investigated surface oxygen vacancy (OVs)-modified Bi 2 MoO 6 /MIL-88B(Fe) heterostructures as a catalyst for dye pollutant rhodamine B (RhB) and model colorless pollutant bisphenol A (BPA) photodegradation. 23 In our previous studies, UiO-66 was used as a catalyst in CWPO and showed excellent catalytic effect ( X phenol = 95%, X H 2 O 2 = 55% in 60 min).…”
Section: Introductionmentioning
confidence: 99%
“…These residuals can be anticipated, and unexplained variations for a normal distribution may originate from a fitted model . The normality of these residuals can be visually assessed using normal probability plots, which compare the predicted and residual responses (Figure a,b). Comparing the experimental and predicted results is crucial in assessing the suitability of the model.…”
Section: Resultsmentioning
confidence: 99%
“…The photocatalytic performance of these heterostructures was examined by analyzing their ability to degrade MB under direct solar light irradiation. The photocatalytic removal of MB using BiOI-based bimetallic MOFs depends on several parameters, making it difficult to perform and manage these experiments; therefore, a robust approach is required to avoid improper and inconsistent results . Statistical modeling and experimental design techniques have been suggested for the analysis and optimization of such experiments, which involve several variables .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific surface area of Ha m ZIF-90 was measured and analyzed by the nitrogen adsorption–desorption curves as shown in Figure 7 a. It could be seen that the isotherm trends for HamZIF-90(0.05), HamZIF-90(0.06), HamZIF-90(0.07), and HamZIF-90(0.08) were similar to the type III isotherm, indicating that HamZIF-90 has mesoporous and macroporous properties owing to the etching of the hydrogel by the high-temperature aqueous solution [ 36 ]. According to the BET model, the specific surface areas of Ha m ZIF-90(0.05), Ha m ZIF-90(0.06), Ha m ZIF-90(0.07), and Ha m ZIF-90(0.08) were 89 m 2 ·g −1 , 91 m 2 ·g −1 , 101 m 2 ·g −1 , and 110 m 2 ·g −1 , respectively, and the specific surface area of ZIF-90 was 204 m 2 ·g −1 .…”
Section: Resultsmentioning
confidence: 99%